Hubungan Iklan Rokok Dengan Perilaku Remaja Laki-Laki Di Kelurahan Desa Limbangan Wetan Kabupaten Brebes - Dewi Sulistyoningrum; Suci Fitriana Pramudya Wardani; Raden Roro Amanda Resti Naranadiya (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Background: Smoking is common among adults and teenagers, especially men. This lifestyle is one of the biggest problems facing the world of health because it causes almost 6 million deaths every year. More than 5 million people die from smoking, while 600 thousand people die from exposure to cigarette smoke. Method: This research uses a quantitative research type, analytical approach, cross-sectional study design. The population in this study were male teenagers in Limbangan Wetan Village, Brebes Regency. Sampling used simple random sampling with a total sample of 30 male teenagers. This research was conducted using the interview method and data collection tools, namely questionnaires. Results: Research shows that the most common age of smokers is 18-24 years old (50%), the highest level of education is high school graduation (56.7%), the highest number of types of smokers smoked is 11-20 cigarettes per day ( 36.7%), 20 respondents were exposed to cigarette advertising (66.7%) and 26 people smoked (86.7%). Conclusion: there is a significant relationship between cigarette advertising and the behavior of adolescent boys in the Limbangan Wetan Village Village, Brebes Regency.